2022
DOI: 10.53660/conj-s30-1155
|View full text |Cite
|
Sign up to set email alerts
|

Letramento em saúde como estratégia de promoção da saúde: um estudo de revisão narrativa

Abstract: O objetivo desse estudo é analisar a contribuição do letramento em saúde para o aumento da eficácia do cuidado em saúde na atenção primaria à saúde e seu impacto na promoção da saúde. Caracteriza-por ser um estudo de revisão bibliográfica narrativa explicativa, descritiva-qualitativa sobre a prática do letramento em saúde na atenção primária à saúde e seus impactos no Sistema Único de Saúde. A pesquisa foi realizada em bases de dados internacionais buscando estudos que discorreram sobre o letramento em saúde, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Vários são os fatores que podem interferir nos padrões nutricionais de um indivíduo e, entre eles, tem sido abordado, atualmente, o conceito de letramento nutricional (LN). De acordo com revisão sistemática realizada por Barbosa SP, et al (2022), um maior nível de LN tem sido relacionado ao maior consumo de frutas, legumes e verduras, além de melhoras em marcadores de risco cardiovascular. Isto significa que quanto maior o LN, melhor tem sido a alimentação dos indivíduos, contribuindo, então, para a prevenção de danos cardiovasculares.…”
Section: Discussionunclassified
“…Vários são os fatores que podem interferir nos padrões nutricionais de um indivíduo e, entre eles, tem sido abordado, atualmente, o conceito de letramento nutricional (LN). De acordo com revisão sistemática realizada por Barbosa SP, et al (2022), um maior nível de LN tem sido relacionado ao maior consumo de frutas, legumes e verduras, além de melhoras em marcadores de risco cardiovascular. Isto significa que quanto maior o LN, melhor tem sido a alimentação dos indivíduos, contribuindo, então, para a prevenção de danos cardiovasculares.…”
Section: Discussionunclassified
“…27 Another aspect questioned to nurses was about the impact generated by the level of HL in the treatment of patients with chronic diseases in PHC, being contemplated the cost; frequency of returns in the unit and hospitalizations; resoluteness and work overload, as also shown by a study. 9 In this sense, national and international studies have shown that HL is directly related to health promotion and prevention of diseases and that when it is insufficient, it contributes to inadequate use of services and provides poor health outcomes. It is also associated with adverse effects on the transition of care, increased prevalence of chronic diseases, and higher costs for health services.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similar findings were also identified in other studies, which showed that in the context of SUS, a great deal of acute illness among users, especially chronic ones, is observed due to lack of information and/or understanding of the information received during the nursing consultation. 5,9 In this perspective, due to the need to expand the knowledge related to this theme, as well as to contribute for professionals to subsidize interventions in the users' HL, this study aimed to explore the perceptions of Primary Care nurses about the importance of assessing Health Literacy during the nursing consultation with the chronically ill.…”
Section: Introductionmentioning
confidence: 99%